Effects of Multiple Ion Reactions Based on a CoSe2/MXene Cathode in Aluminum‐Ion Batteries. Issue 17 (21st March 2023) - Yuan, Zeyu; Lin, Qifeng; Li, Yilin; Han, Wei; Wang, Lili
Abstract: Rechargeable aluminum‐ion batteries (RAIBs) have emerged as a promising battery storage technology owing to their cost‐effectiveness, operational safety, and high energy density. However, their actual capacity is substantially lower than their true capacity and their cycling stability is poor. Therefore, understanding the energy‐storage mechanism may contribute to the successful design of a stable electrode material, on which the performance can be optimized. The aim of this study is to investigate AlCl4 − ions in transition metal cathode materials and mechanisms that enable for their high‐energy‐storage potential and low Coulombic efficiency. Results of theoretical analysis and experimental verification show that a multi‐ion transport mechanism is responsible for the electrochemical behavior of the battery. The lattice distortion of CoSe2 caused by AlCl4 − ion intercalation, has a considerable effect on the initial stability of the battery. MXene as a support material reduces the size of CoSe2 growing on its surface, effectively inhibiting the lattice distortion caused by the interaction with the aluminum‐anion complex, thus addressing the issues of poor reversibility, cycle instability, and low Coulombic efficiency of the battery. Hence, understanding the impact of MXene on the battery may aid in further improving the design of electrode materials. Abstract : An aluminum‐ion cathode material based on an array of MXene lamellar CoSe2 nanoparticles is designed and synthesized. The lattice distortion brought by the AlCl4 − ion embedding has a serious impact on the initial stability of the battery, and such distortion consumes extra energy, making it difficult for the Coulombic efficiency to reach close to 100%.